Cineangiographic and pathological features of the infarct related vessel in successful and unsuccessful thrombolysis. Issue 5 (May 1989) - Onodera, T; Fujiwara, H; Tanaka, M; Wu, D J; Matsuda, M; Takemura, G; Ishida, M; Kawamura, A; Kawai, C
Abstract : The postmortem histology and the results of cineangiography after selective intracoronary thrombolysis in vessels that were recanalized and in those that were not were compared in 21 patients who died within seven days (mean 2 days) of selective intracoronary thrombolysis. There was a persistent intraluminal thrombus in the infarct related coronary artery in five of six segments in which recanalisation was unsuccessful and in one of 15 segments in which recanalisation was successful. Rupture and haemorrhage of the atheromatous plaque were seen in most of the infarct related segments, both in those in which recanalisation was achieved and in those in which it was not. Irregular narrowing and filling defects on the coronary cineangiograms were associated with rupture and haemorrhage of the atheromatous plaque. These results suggest that failure of coronary thrombolysis to recanalize the infarct related artery does not indicate that the occlusion was not caused by thrombus.